Legal Accountability for Deepfake Abuse Against Women and Children in Indonesia: A Regulatory Challenge in the Era of Artificial Intelligence - Wahyu Kurniadi (Green Publisher, 2025)
The development of artificial intelligence (AI) has given rise to deepfake technology capable of realistically manipulating images, sounds, and videos. While this technology offers benefits, it also poses new threats in the form of digital identity abuse, often targeting women and children, as vulnerable groups. This study aims to analyze legal liability for deepfake abuse and formulate an adaptive regulatory model in Indonesia. The study uses a normative juridical method with a statutory, conceptual, and comparative regulatory approach. The results indicate that existing legal regulations do not specifically regulate deepfake crimes, creating a legal vacuum in victim protection and law enforcement. This study proposes a regulatory model that integrates the responsibilities of the state, digital platforms, and AI developers by strengthening oversight mechanisms, early detection, content removal, and victim rights restoration. This model is expected to create adaptive legal protection for the development of digital technology in Indonesia.